Utilizing liposomal encapsulation approach to address nephrotoxic challenges of colistimethate sodium through a preclinical study - Mektrirat, Raktham; Paengjun, Noppanut; Chongrattanameteekul, Peerawit; Umsumarng, Sonthaya; Cheunsri, Suppara; Photichai, Kornravee; Lewchalermvong, Kittima; Sansamur, Chalutwan; Okonogi, Siriporn; Katip, Wasan (Frontiers in Pharmacology, 2023)
The use of Colistin, a last-resort antimicrobial drug, carries the risk of acute kidney injury. The objective of the study was to assess the effectiveness of colistin-encapsulated liposomes (CL) in reducing nephrotoxicity. Additionally, a liposomal preparation of colistimethate sodium was formulated using the reverse phase evaporation method with a 3:1 ratio of phospholipids to cholesterol. The liposomal properties were evaluated using scanning electron microscopy, photon correlation spectroscopy, and release kinetic assay. The killing kinetics of the formulations on embryonic kidney 2 This is a provisional file, not the final typeset article cells were assessed using in vitro MTT reduction assay. The nephrotoxicity of CL and colistimethate sodium solution (CS) was evaluated in vivo by administering a dose of 20 mg/kg to rats every 12 hours for 3 days, with a negative control group receiving a 0.9% saline solution (NSS). The study results revealed that monodisperses of CL showed a smooth surface and distinct boundaries, with an average size of 151.50 ± 0.46 nm and a narrow size distribution of 0.25 ± 0.01. The liposomal particles showed high entrapment efficiency of 96.45 ± 0.41%, with a ζ-potential of -60.80 ± 1.01 mV and a release rate of 50% of colistimethate sodium within the first 480 minutes. The CL induced nephrocytotoxicity in a concentration-and time-dependent manner. However, CS had notably lower IC50 values compared to its liposome preparations at 48 and 72 hours (p < 0.05). In vivo study results show that serum levels of symmetric dimethylarginine (SDMA) and total white blood cell count (WBC) were significantly lower in the CL group (SDMA = 8.33 ± 1.70 µg/dL; WBC = 7.29 ± 0.99 log10 cells/mL) compared to the CS group (SDMA = 15.00 ± 1.63 µg/dL; WBC = 9.73 ± 0.51 log10 cells/mL). Our study findings enhance the understanding of the safety profile of CL and its potential to improve patient outcomes through the use of liposomal colistin medication. Additional clinical studies are necessary to establish the optimal safety regiment in humans.